International Chamber of Commerce (ICC) Sebagai Alternatif Penyelesaian Sengketa Bisnis Internasional - Chika Ardellia Khanza; Cyrill Milanesta Hisyam; Kaia Azahra Putri Aimar; Safa Aqila Ilzan; Tasfiyah Azzahra (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The rapid growth of international trade has increased the possibility of cross-border business disputes. Differences in legal systems and jurisdictions often make dispute resolution through national courts less effective. As a result, international arbitration has developed as a more flexible and efficient alternative dispute resolution mechanism. One of the most widely used institutions is the International Chamber of Commerce (ICC) through the ICC International Court of Arbitration. This study aims to analyze the role of the ICC in resolving international business disputes and to examine the mechanism and effectiveness of ICC Arbitration as an alternative dispute resolution method outside the court system. This research employs a normative legal research method using statutory and conceptual approaches. The findings show that the ICC plays an important role in providing a neutral and professional dispute resolution forum. Furthermore, ICC Arbitration offers several advantages, including procedural flexibility, confidentiality, and the ease of enforcing arbitral awards through the 1958 New York Convention